Optoacoustic Imaging of Skin - Schwarz, M.; Aguirre, J.; Omar, M.; Ntziachristos, V. (Elsevier Inc., 2016)
The optical imaging techniques available for clinical skin imaging are fundamentally limited in their depth scope to a few hundred microns and face difficulties in their functional and molecular imaging capabilities. Furthermore, histopathological analysis is still the only method of choice to accurately diagnose several skin diseases. Raster-scan optoacoustic mesoscopy (RSOM) is a high-resolution optical imaging technique that can penetrate several millimeters in tissues, overcoming the limitation of the classical optical techniques. Hence, RSOM has the potential to reduce the number of needed biopsies and thus provide cheaper, faster and less invasive skin healthcare. In this chapter, we present the latest advances in RSOM instrumentation and we showcase its imaging capabilities.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Angiogenesis; Dermatology; Melanoma; Optical imaging; Optoacoustic mesoscopy